Twitch user perceptions, attitudes and behaviours in relation to food and beverage marketing on Twitch compared with YouTube. (27th April 2021) - Pollack, Catherine C.; Gilbert-Diamond, Diane; Emond, Jennifer A.; Eschholz, Alec; Evans, Rebecca K.; Boyland, Emma J.; Masterson, Travis D.
Abstract: Influencer marketing may be amplified on livestreaming platforms (e.g., Twitch) compared with asynchronous social media (e.g., YouTube). However, food and beverage marketing on Twitch has not been evaluated at a user level. The present study aimed to compare users' self-reported exposure to food marketing and associated attitudes, consumption and purchasing behaviours on Twitch compared with YouTube. A survey administered via social media was completed by 621 Twitch users (90 % male, 64 % white, 69 % under 25 years old). Of respondents, 72 % recalled observing at least one food or beverage advertisement on Twitch. There were significant differences in the recall of specific brands advertised on Twitch ( P < 0⋅01). After observing advertised products, 14 % reported craving the product and 8 % reported purchasing one. In chat rooms, 56 % observed conversations related to food and 25 % participated in such conversations. There were significant differences in the number of users who consumed various products while watching Twitch ( P < 0⋅01). Of users who frequented YouTube ( n 273), 65 % reported negative emotions when encountering advertising on YouTube compared with 40 % on Twitch ( P < 0⋅01). A higher proportion felt Twitch's advertising primarily supported content creators (79 v . 54 %, P < 0⋅01), while a higher proportion felt that YouTube's advertising primarily supported the platform (49 v . 66 %, P < 0⋅01). The findings support that food marketing exposures on Twitch are noticeable, less bothersome to users and influence consumption and purchasing behaviours. Future studies are needed to examine how the livestreaming environment may enhance advertising effectiveness relative to asynchronous platforms.